Effectiveness of Root System of Grasses Used in Soil Conservation in Paundi Khola Sub Watershed of Lamjung District, Nepal - Kafle, Gandhiv; Balla, Mohan K (The Initiation, 2010)
The study was carried out in Paundi Khola Sub-watershed of Lamjung District, with the objective of evaluating the effectiveness of root system of grasses used in soil conservation. Different root parameters were recorded through direct field measurement. Key informant's survey, semi-structured walk and focus group discussions were also undertaken to acquire relevant information on pattern of retaining grasses, insect/pest condition, local uses of grasses, perceived weeds and perception of farmers on different issues. Stylo and Molasses are most effective in armouring the slope against surface erosion from both runoff and rain splash due to their dense surface cover, low canopy and small leaves. Broom Grass and Napier are most effective in reinforcing the soil by providing a network of strong roots that increases the soil's resistance to shear. Broom Grass can moderately support the soil mass by its strong and long fibrous roots. Broom Grass can bind average 3.8 cu. m. soil, and that for napier, stylo, and molasses are 0.37 cu. m., 0.45 cu. m. and 0.04 cu. m. soil respectively. It was found that farmers plant the improved varieties of grasses primarily for forage due to high foliage content. Soil conservation is second priority. A combination of improved varieties of grasses and natural grasses helps to conserve soil and moisture more effectively than single-use of grass species on marginal land. Key Words: Effectiveness, Improved grass species, Root, Soil conservation, Napier, Molasses, Stylo, Broom grass. DOI: 10.3126/init.v2i1.2533 The Initiation Vol.2(1) 2008 pp121-129